Beyond The Green School: Integrating Islamic Ecopedagogy and Eco-Spiritual Character Education - Al-Kaff, Abdulloh Muhamad; Widodo, Sembodo Ardi (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
Environmental education in schools often emphasizes physical greening and routine behavior while giving insufficient attention to ecological awareness as a process of spiritual and character formation. Previous green-school studies have examined program implementation and observable environmental practices, leaving limited empirical explanation of how Islamic theological values are translated into pedagogical practices and internalized as students' ecological character. This study examined the integration of Islamic ecopedagogy and eco-spiritual character education at SMP Citra Alam Gunungkidul. Using a qualitative case study design, data were collected from eight purposively selected informants through semi-structured interviews, classroom and schoolyard observations, and document analysis. Data were analyzed using Miles, Huberman, and Saldaña's interactive model through condensation, coding, categorization, thematic synthesis, and framework construction. The findings revealed that tawḥīd functioned as the central framework connecting ecological knowledge and nature-based experiences as a form of amānah, shukr, and khalīfah responsibility. This process operated through six interconnected elements: tawḥīd as a value foundation, ecological literacy, nature-based learning, ecological habituation, teacher role modeling, and spiritual reflection. Together, these elements formed an interpretive Eco-Spiritual Character education framework. The study implies that Islamic environmental education should integrate theological meaning, ecological experience, consistent habituation, teacher modeling, and structured reflection into curriculum design and school environmental programs.